Fear of falling in community-dwelling older adults presenting to the emergency department for minor injuries: Impact on return to the ED and future falls. Issue 5 (September 2020) - Lanoue, Marie-Pier; Sirois, Marie-Josée; Perry, Jeffrey J.; Lee, Jacques; Daoust, Raoul; Worster, Andrew; Hegg, Sandrine; Carmichael, Pierre-Hugues; Brousseau-Turcotte, Audrey-Anne; Émond, Marcel
ABSTRACT: Objectives: 1) To characterize mild, moderate, and severe fear of falling in older emergency department (ED) patients for minor injuries, and 2) to assess whether fear of falling could predict falls and returns to the ED within 6 months of the initial ED visit. Methods: This study was part of the Canadian Emergency and Trauma Initiative (CETI) prospective cohort (2011–2016). Patients ages ≥ 65, who were independent in their basic daily activities and who were discharged from the ED after consulting for a minor injury, were included. Fear of falling was measured by the Short Falls Efficacy Scale International (SFES-I) in order to stratify fear of falling as mild (SFES-I = 7-8/28), moderate (SFES-I = 9-13/28), or severe (SFES-I = 14-28/28). Many other physical and psychological characteristics where collected. Research assistants conducted follow-up phone interviews at 3 and 6 months' post-ED visit, in which patients were asked to report returns to the ED. Results: A total of 2, 899 patients were enrolled and 2, 009 had complete data at 6 months. Patients with moderate to severe fear of falling were more likely to be of ages ≥ 75, female, frailer with multiple comorbidities, and decreased mobility. Higher baseline fear of falling increased the risk of falling at 3 and 6 months (odds ratio [OR]-moderate-fear of falling: 1.63, p < 0.05, OR-severe-fear of falling 2.37, p < 0.05). Fear of falling positive predictive values for return to the ED or future falls were 7.7% to 17%. Conclusion: Although a high fear of falling is associated with increased risk of falling within 6 months of a minor injury in older patients, fear of falling considered alone was not shown to be a strong predictor of return to the ED and future falls.